2021
DOI: 10.1016/j.vph.2021.106856
|View full text |Cite
|
Sign up to set email alerts
|

In silico Nigellidine (N. sativa) bind to viral spike/active-sites of ACE1/2, AT1/2 to prevent COVID-19 induced vaso-tumult/vascular-damage/comorbidity

Abstract: COVID-19, a global-pandemic binds human-lung-ACE2. ACE2 causes vasodilatation. ACE2 works in balance with ACE1. The vaso-status maintains blood-pressure/vascular-health which is demolished in Covid-19 manifesting aldosterone/salt-deregulations/inflammations/endothelial-dysfunctions/hyper-hypo- tension, sepsis/hypovolemic-shock and vessel-thrombosis/coagulations. Here, nigellidine, an indazole-alkaloid was analyzed by molecular-docking for binding to different Angiotensin-binding-proteins (enzymes, ACE1(6en5)/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Among several medicinal plants, N. sativa is regarded as one of the most valuable nutrient-dense herbs in human history, and numerous scientific investigations are underway to confirm its traditional use ( 42 ). At the same time, researchers found that N. sativa seeds can be utilized as nutritional supplements for COVID-19 patients as an adjuvant treatment, which set off an upsurge of research on N. sativa seeds ( 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among several medicinal plants, N. sativa is regarded as one of the most valuable nutrient-dense herbs in human history, and numerous scientific investigations are underway to confirm its traditional use ( 42 ). At the same time, researchers found that N. sativa seeds can be utilized as nutritional supplements for COVID-19 patients as an adjuvant treatment, which set off an upsurge of research on N. sativa seeds ( 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 11 studies (25.58%) approached the spike glycoprotein as target protein, being the alkaloids analyzed the following: crambescidin 826, cryptospirolepine, deoxynortryptoquivaline, ergotamine, hyoscyamine, nicotine docking on soluble angiotensin‐converting enzyme II receptor in complex with spike (S) protein of Indian SARS‐CoV‐2 (sACE2‐INS1), nigellidine, norbolidine, pallidine, piperine and quinadoline B (Borquaye et al, 2020; El‐Demerdash et al, 2021; Firdiana et al, 2021; Gyebi et al, 2020; Ismail et al, 2021; Selvaa Kumar, Kumar, & Wei, 2020; Maiti, Banerjee, & Kanwar, 2021; Maiti, Banerjee, Nazmeen, Kanwar, & Das, 2020; Mao, Bie, Xu, Wang, & Gao, 2021; Ogunyemi et al, 2020; Skariyachan, Gopal, Muddebihalkar, & Uttarkar, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The alkaloids nicotine, nigellidine, norboldine, piperine, quinadoline A and trytoquivaline showed binding capacity to the angiotensin‐converting enzyme II (ACE2) (Firdiana et al, 2021; Ismail et al, 2021; Maiti et al, 2021; Maurya, Kumar, Prasad, Bhatt, & Saxena, 2020; Selvaa Kumar, Kumar, & Wei, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spike protein (S protein) of SARS-CoV binds to cell surface ACE2 receptors (9). ACE1, homologous to the ACE2 gene, may be involved in the progression of diseases caused by several human coronaviruses (10,11). Transmembrane serine protease 2 (TMPRSS2), a member of the serine protease family, facilitates human coronavirus infections (SARS-CoV and SARS-CoV-2) via proteolytic cleavage of the ACE2 receptor, which promotes viral uptake and cleavage of coronavirus spike glycoproteins, activating glycoproteins for host cell entry (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%